ANALISIS RANTAI PASOK DAN RANCANG BANGUN SISTEM KETERTELUSURAN KOPI ROBUSTA BERBASIS ANDROID - Alhabsyi, Mohamad Fadel; Pertiwi, Setyo; Pujantoro, Lilik (Jurnal Keteknikan Pertanian, 2024)
Robusta coffee is the most widely cultivated coffee commodity in Indonesia. In the East Bolaang Mongondow Regency, the problem at the supplier level is limited market information, which makes the coffee beans' quality inconsistent, impacting the price and product quality image. This research aims to identify supply chain structure models and members, added value, and design a traceability system to support product quality validation. Robusta coffee supply chain participants and their interactions were identified at the Modayag coffee plantation in East Bolaang Mongondow. The data were collected through observations, interviews, and field studies. Supply chain analysis was performed using the Vorst method and the added value was calculated using the Hayami method. The traceability system design follows the system development lifecycle method. The findings indicate that the Robusta coffee supply chain in East Bolaang Mongondow Regency includes farmers, collector traders, processing plants, the retail industry, coffee roasteries, and consumers. Farmers profit from selling perfectly ripe wet coffee beans 42-43%, wet mixed coffee beans (8%), and dry mixed coffee beans 63-71%. A traceability system named Kinton was successfully developed and integrated with the Firebase database to store all information.